Antibacterial Activityof Aqueous And Ethanolic Leaf Extracts Of Vernonia Amygdalina On Selected Species Of Gram Positive And Gram Negative Bacteria - Bukar, AM; Isa, MA; Bello, HS; Abdullahi, AS (International Journal of Environment, 2013)
The phytochemical screening and antibacterial activity of ethanolic and Methanolic leaves extract of Vernonia amygdalina against five clinical isolates (Staphylococcus aureus, E. coli, Pseudomonas species, Salmonella species and Proteus species) was determined using standard method of analysis. The results of the antibacterial activity of ethanol, methanol and aqueous extract of leaves of V. amygdalina have diameters ranging between 0.4 to 10mm. The plant extracts from the plants had profound activities against gram-positive than gram negative bacteria. From the above studies, it has clearly indicated that V. amygdalina extract may represent new sources of antibacterial drug, if the phytoactive components are purified and proper dosage are determined for administration. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 147-152 DOI: http://dx.doi.org/10.3126/ije.v2i1.9217